Does attachment predict the outcome of cognitive processing therapy for posttraumatic stress disorder in adolescent patients with interpersonal traumatization?. (4th July 2022) - Rimane, Eline; Steil, Regina; Renneberg, Babette; Rosner, Rita
Abstract: The attachment has emerged as a significant predictor of psychotherapy outcome. However, studies on trauma-focused treatments and adolescent samples are sparse. We analyzed the data of 43 adolescents and young adults (aged 14–21 years) with clinically relevant abuse-related posttraumatic stress disorder (PTSD) who were undergoing developmentally adapted cognitive processing therapy (D-CPT) within a multicenter, randomized clinical trial (German Clinical Trials Register; identifier: DRKS00004787). Besides clinician-rated posttraumatic stress symptoms (PTSS), attachment-related (AR) anxiety and AR avoidance were assessed using self-reports before and after treatment as well as at three-month and six-month follow-ups. Baseline attachment did not predict any changes in PTSS severity. Averaging across all assessment points, overall higher posttraumatic avoidance was associated with greater baseline AR avoidance in D-CPT. In terms of change in attachment during the trial, a greater reduction of attachment insecurities was associated with a greater reduction of PTSS severity. Results are compared with those of the control group, a wait-list condition with treatment advice (WL/TA; N = 42). AR anxiety was more often a significant variable in the models in WL/TA, whereas AR avoidance was in D-CPT. Our study does furnish initial insights into the role of attachment during trauma-focused treatment with abused adolescents and young adults. Trial registration: German Clinical Trials Register identifier: DRKS00004787.